Neuromuscular Disorders in the Intensive Care Unit - Damian, MS; Hilton-Jones, D (Wiley-Blackwell, 2011)
Patients in the intensive care unit (ICU) with neuromuscular disorders are either admitted for an acute life-threatening disease of new onset such as Guillain-Barré syndrome, or for a complication of a severe pre-existing condition such as muscular dystrophy, or they develop a neuromuscular disorder as a consequence of critical illness, i.e. so-called "ICU-associated weakness." This chapter provides an introduction to the specific requirement of these patients needed to improve their outcomes after ICU treatment. © 2011 Blackwell Publishing Ltd.